AVALIAÇÃO DO MODELO DE REGRESSÃO POTÊNCIA NO CRESCIMENTO DE NOPALEA COCHENILLIFERA EM FUNÇÃO DO FRACIONAMENTO DO CLADÓDIO - LUCENA, Leandro Ricardo Rodrigues de; PEREIRA, Juliana De Souza; LEITE, Maurício Luiz de Mello Vieira (Brazilian Journal of Biometrics, 2018)
In this work we evaluate the growth length of bud of Nopalea cochenillifera using five different forms of crops through power regression model. The adjusted models showed very similar estimates of lengths observed independent using of planting method. The power regression models showed coefficient of determination of model high 99.65% (treatment 1), 99.82% (treatment 2), 99.26% (treatment 3), 99.93% (treatment 4) and 99.34% (treatment 5). The power regression model proved effective to model the growth length of Nopalea cochenillifera of bud can generate strategies and plans for future plantings, as well useful information as: appropriate crop management, increased plant growth period and pest control.